2006
DOI: 10.1093/jmedent/43.6.1261
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofEhrlichia,Borrelia, andRickettsialAgents inAmblyomma americanum(Acari: Ixodidae) Collected from Nine States

Abstract: Ambyomma americanum (L.) (Acari: Ixodidae) is an aggressive tick that feeds on humans during all postembryonic life stages. In many regions of the United States, it is the tick most commonly found attached to humans. Public health interest has grown recently, due to the recognition of new human pathogens transmitted by A. americanum and the expanding distribution of the tick. A. americanum is a vector of several bacteria pathogenic to humans. Ehrlichia chaffeensis and Ehrlichia ewingii cause moderate-to-severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
41
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
8
41
1
Order By: Relevance
“…The average prevalence of Rickettsia in all parks over the three-year collection period was 57.1% of individual host-seeking LSTs (845/1479). This is similar to previously reported prevalence of the organism in LSTs in other geographic areas in the southeastern United States [1]. R. amblyommii was the only Rickettsia spp.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The average prevalence of Rickettsia in all parks over the three-year collection period was 57.1% of individual host-seeking LSTs (845/1479). This is similar to previously reported prevalence of the organism in LSTs in other geographic areas in the southeastern United States [1]. R. amblyommii was the only Rickettsia spp.…”
Section: Resultssupporting
confidence: 91%
“…This organism has been identified in many species of Amblyomma ticks including Amblyomma americanum, Amblyomma maculatum and Amnlyomma cajennense. The preferred tick host in the United States appears to be the lone star tick (LST), A. americanum, and has been identified in 41.2% [1] to 64.5% [2] of host-seeking A. americanum collected from diverse geographic regions of the United States. The organism was reportedly highly prevalent (89%) in pools of the immature life stages of A. americanum by polymerase chain reaction (PCR) [3] and was detected in 66.5% to 80.5% of A. americanum pools that were directly parasitizing humans [4].…”
Section: Introductionmentioning
confidence: 99%
“…(AF031496 and AY3888929) from A. americanum . Moreover, Mixson et al reported that “ R. amblyommi ” was transovarially transmitted and had a prevalence in A. americanum that was similar to what we found in our present and previous studies [27].…”
Section: Discussionsupporting
confidence: 92%
“…R. andeanae” (from 64–69%) have been reported in specimens of Amblyomma parvum collected in Argentina and Brazil (Pacheco et al, 2007 and Nieri-Bastos et al, 2014). These percentages are also consistent with the frequency of R. amblyommii , a vertically-transmitted rickettsial symbiont (Ponnusamy et al, 2014) detected in 37–57% of Amblyomma americanum ticks collected in Florida (Mixson et al, 2006 and Sayler et al, 2014), 45–60% in Georgia (Mixson et al, 2006 and Clay et al, 2008), 60–65% in Kentucky (Clay et al, 2008 and Jiang et al, 2010), 66–71% in Maryland (Jiang et al, 2010 and Zhang et al, 2012), 55–60% in North Carolina (Mixson et al, 2006, Clay et al, 2008 and Smith et al, 2010) and 70–82% in Virginia (Jiang et al, 2010 and Nadolny et al, 2014). …”
Section: Discussionsupporting
confidence: 79%